Exploring the Impenetrability of Narrative: A Study of Linguistic Modality in Alice Munro's Early Fiction - Somacarrera, Pilar (Studies in Canadian Literature, 1996)
An undercurrent of obscurity flows throughout much of Alice Munro's fiction. In fact, recent Munro criticism has noted the author's increasing involvement with a poetics of uncertainty and a rhetoric of mistrust. Modality -- recognized as one of the most fruitful areas of intersection between linguistic and literary styles -- provides the basis for an examination of the stylistic approach taken in three of Munro's early stories: "Something I've Been Meaning to Tell You," "Royal Beatings," and "Half a Grapefruit." Close study of these early narratives considering both epistemic and deontic modality reveals that the epistemic commitment encoded in the stories is often weak, that Munro uses modality to encode gossip, and further, that often the boundaries between epistemic and deontic meaning are unclear, resulting in a pervasive narratorial ambiguity. Such stylistic analysis of the role of modality in these texts also leads to the discovery that knowledge is most often the theme of these narratives.